Factors Influencing Sexual Behavior Among High School in South Sulawesi - Muthahharah; Muh. Irwan, (Jurnal MSA ( Matematika dan Statistika serta Aplikasinya), 2025)
Factors Influencing Sexual Behavior Among High School In South Sulawesi. Sexual behavior among adolescents is a crucial issue in public health and education, particularly among high school students. This study aims to analyze the factors influencing sexual behavior among high school or equivalent adolescents in South Sulawesi. The analyzed variables include knowledge of sexual behavior, media use, parental roles, peer influence, and religious knowledge. This study employs a quantitative approach using a survey method with a cross-sectional design. Data were collected from 1,069 respondents, who were randomly selected using a structured questionnaire. The data analysis was conducted using Exploratory Factor Analysis (EFA). The study results identify five factors comprising 16 indicators. Based on these findings, three main components emerged from the observed indicators: (1) the role of parents in supervision and family interaction; (2) morality and the influence of religious values; and (3) sexual knowledge and media utilization. These three components further led to the formation of three new factors: Parenting, Religiomorality, and Media Literacy. The findings of this study can serve as a foundation for developing programs in schools and communities aimed at providing preventive, curative, and promotive services related to adolescent sexual behavior.